Ghrelin Axis Reveals the Interacting Influence of Central Obesity and Hypertension - Yu, Angus P.; Ugwu, Felix N.; Tam, Bjorn T.; Lee, Paul H.; Lai, Christopher W.; Wong, Cesar S. C.; Siu, Parco M. (Frontiers in Endocrinology, 2018)
Objective: This study aimed to investigate how central obesity and hypertension modulate unacylated ghrelin (UnAG), acylated ghrelin (AG), obestatin, growth hormone (GH), and the ratios of UnAG/obestatin, AG/obestatin and total ghrelin/obestatin. Methods: Circulatory abundances of UnAG, AG, obestatin and GH were determined in 387 Hong Kong Chinese female adults with age between 24 to 86 years based on a 2 x 2 factorial design of hypertension (blood pressure ≥140/90 mmHg) and central obesity (waist circumference or WC ≥80 cm). Participants were categorized as neither hypertensive nor centrally obese (NHNO; n = 105), hypertensive but not centrally obese (HNO; n = 102), centrally obese but not hypertensive (NHO; n = 74) and hypertensive and centrally obese (NO; n = 106). Pearson’s correlation analyses were performed to detect the association between the peptides examined with WC and blood pressure. The main and interaction effects of hypertension and central obesity were examined by generalized estimating equations analyses. Results: Correlation analyses revealed that systolic blood pressure was negatively correlated with AG/obestatin, UnAG/obestatin and total ghrelin/obestatin ratios, AG, total ghrelin and GH, while diastolic blood pressure was negatively correlated with UnAG/obestatin, total ghrelin/obestatin ratios and GH. WC was negatively correlated with AG/obestatin, UnAG/obestatin and total ghrelin/obestatin ratios, UnAG, AG, total ghrelin, GH and obestatin. Interaction effects of hypertension and central obesity were observed on UnAG/obestatin, AG/obestatin and total ghrelin/obestatin ratios, and obestatin. Obestatin in NHO group was significantly higher compared to NHNO and HO groups. UnAG/obestatin, AG/obestatin and total ghrelin/obestatin ratios were higher in NHNO group compared to HNO and HO groups. Main effects of central obesity and hypertension were observed in UnAG, total ghrelin and GH. The HO group manifested the lowest level of UnAG, total ghrelin and GH among all the groups studied. Main effect of hypertension was observed on AG, suggesting that hypertensive individuals exhibited lower levels of AG regardless of central obesity. Conclusion: Circulatory ghrelin gene products and GH exhibit different modes of modulation in response to the co-manifestation of multiple cardiovascular risk factors compared with a single risk factor alone.